2020
DOI: 10.1039/d0fo01598a
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and pharmacological activities of the natural health-benefiting compound diosmin

Abstract: Diosmin is a famous natural flavonoid for treating chronic venous insufficiency and varicose veins. Recently, the extensive study indicates that diosmin possesses diverse pharmacological activities, including anti-inflammation, anti-oxidation, anti-diabetes, anti-cancer,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 167 publications
1
42
0
1
Order By: Relevance
“…The agent for AD treatment through upregulates NEP should be safe and effective. Diosmin is a flavonoid isolated from citrus that is widely used in the clinical management of chronic venous insufficiency and varicose veins 55 . Many studies showed that diosmin has various pharmacological activities, including anti-inflammation, anti-diabetes, anti-cancer and organ protection 55 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agent for AD treatment through upregulates NEP should be safe and effective. Diosmin is a flavonoid isolated from citrus that is widely used in the clinical management of chronic venous insufficiency and varicose veins 55 . Many studies showed that diosmin has various pharmacological activities, including anti-inflammation, anti-diabetes, anti-cancer and organ protection 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Diosmin is a flavonoid isolated from citrus that is widely used in the clinical management of chronic venous insufficiency and varicose veins 55 . Many studies showed that diosmin has various pharmacological activities, including anti-inflammation, anti-diabetes, anti-cancer and organ protection 55 . I3C is a compound isolated from cruciferous vegetables and is used as a dietary supplement.…”
Section: Discussionmentioning
confidence: 99%
“…Hesperidin, one of the principal polyphenols in lemon, have been shown to possess various biological properties, such as anti-oxidant, anti-inflammatory, and anti-cancer effects [19][20][21]. Diosmin, eriocitrin, and narirutin are also reported to contribute to health care [22][23][24]. In addition, the supplemental dietary fibers influence the activity and composition of intestinal microflora, which are closely related to our health.…”
Section: Introductionmentioning
confidence: 99%
“…Diosmin is a well-known natural flavonoid used for the treatment of chronic venous insufficiency and varicose veins. Numerous recent studies showed that diosmin exerts various pharmacological activities including anti-inflammatory, antioxidative, antidiabetic, anticancer, antimicrobial, liver-protective, neuroprotective, cardiovascular-protective, kidney-protective, and retina-protective effects ( 132 , 133 ).…”
Section: Epigenetic Effects Of Flavonoids During Cancermentioning
confidence: 99%